Diagnostic Yield of Universal Urine Toxicology Screening in an Unselected Cohort of Stroke Patients. - Rizwan Kalani; Eric M Liotta; Shyam Prabhakaran (PLoS ONE)
Background Illicit drug use increases the risk of cerebrovascular events by a variety of mechanisms. A recent report suggested that universal urine toxicology (UTox) screening of patients with stroke may be warranted. We aimed to evaluate the diagnostic yield of urine drug screening among unselected patients admitted with acute stroke or transient ischemic attack (TIA). Methods Using a single-center prospective study design, we evaluated consecutive patients with acute ischemic stroke, TIA, intracerebral hemorrhage (ICH), or subarachnoid hemorrhage (SAH) over one year. Urine samples were collected within 48 hours of admission and analyzed for common classes of abused drugs. Prevalence of positive UTox screening was determined. We evaluated whether baseline demographics and clinical factors were associated with UTox results. Results Of 483 eligible patients (acute ischemic stroke 66.4%; TIA 18.8%; ICH 7.7%; SAH 7.0%), 414 (85.7%) completed UTox screening. The mean (standard deviation) age was 65.1 (15.6) years, 52.7% were male, and 64.3% were Caucasian. Twenty-two (4.6%) patients had positive screening-cannabinoids were detected in 13 cases (3.1%), cocaine in 5 cases (1.2%), amphetamines in 1 case, and phencyclidine in 1 case. The highest yield (14.1%) was observed in patients < 60 years old with history of tobacco use while it was < 5% in the remaining subgroups (p<0.01). Conclusions Consistent with current guidelines, a selective approach to UTox screening should be pursued in acute stroke evaluation. The highest diagnostic yield is likely to be for cannabinoids and cocaine testing in younger patients with a history of concurrent tobacco use.